2021
DOI: 10.1155/2021/5294627
|View full text |Cite|
|
Sign up to set email alerts
|

MKA: A Scalable Medical Knowledge-Assisted Mechanism for Generative Models on Medical Conversation Tasks

Abstract: Using natural language processing (NLP) technologies to develop medical chatbots makes the diagnosis of the patient more convenient and efficient, which is a typical application in healthcare AI. Because of its importance, lots of researches have come out. Recently, the neural generative models have shown their impressive ability as the core of chatbot, while it cannot scale well when directly applied to medical conversation due to the lack of medical-specific knowledge. To address the limitation, a scalable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Liu et al 54 proposed an effective technique by auto encoding knowledge graphs for multimodal medical report generation using a knowledge-driven encoder and a knowledge-driven decoder. Similarly, Liang et al 55 presented a lightweight as well as a scalable mechanism using the transformer and BERT-GPT architecture to integrate the medical knowledge into different neural generative models on the MedDG and the MedDialog(CN) dialogue corpora. Lin et al 53 proposed a low-resource medical dialogue-generating system along with a Graph-Evolving Meta-Learning (GEML) framework that learns to evolve the commonsense graph for reasoning disease-symptom connections.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al 54 proposed an effective technique by auto encoding knowledge graphs for multimodal medical report generation using a knowledge-driven encoder and a knowledge-driven decoder. Similarly, Liang et al 55 presented a lightweight as well as a scalable mechanism using the transformer and BERT-GPT architecture to integrate the medical knowledge into different neural generative models on the MedDG and the MedDialog(CN) dialogue corpora. Lin et al 53 proposed a low-resource medical dialogue-generating system along with a Graph-Evolving Meta-Learning (GEML) framework that learns to evolve the commonsense graph for reasoning disease-symptom connections.…”
Section: Related Workmentioning
confidence: 99%
“…Liu et al 54 proposed an effective technique by auto encoding knowledge graphs for multimodal medical report generation using a knowledge-driven encoder and a knowledge-driven decoder. Similarly, Liang et al 55 presented a lightweight as well as a scalable mechanism using the transformer and BERT-GPT architecture to integrate the medical knowledge into different neural generative models on the MedDG and the…”
Section: Generic Responsementioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%